Models and solution methods for the uncapacitated r‐allocation p‐hub equitable center problem. (19th July 2017) - Peiró, Juanjo; Corberán, Ángel; Laguna, Manuel; Martí, Rafael
Abstract: Hub networks are commonly used in telecommunications and logistics to connect origins to destinations in situations where a direct connection between each origin–destination (o‐d) pair is impractical or too costly. Hubs serve as switching points to consolidate and route traffic in order to realize economies of scale. The main decisions associated with hub‐network problems include (1) determining the number of hubs ( p ), (2) selecting the p ‐nodes in the network that will serve as hubs, (3) allocating non‐hub nodes (terminals) to up to r ‐hubs, and (4) routing the pairwise o‐d traffic. Typically, hub location problems include all four decisions while hub allocation problems assume that the value of p is given. In the hub median problem, the objective is to minimize total cost, while in the hub center problem the objective is to minimize the maximum cost between origin–destination pairs. We study the uncapacitated (i.e., links with unlimited capacity) r ‐allocation p ‐hub equitable center problem (with 1 < r < p ) and explore alternative models and solution procedures.